(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A simple, precise, accurate and reproducible RP-HPLC method has been developed for determination of Valsartan in Tablet dosage form. A Perkin Elmer HPLC series 200 with software Perkin Elmer total chrome navigator was used. The C-18 (Kromasil, 250 × 4.6 mm) having particle size of 5µm was used. The gradient mobile phase was selected consisting of solution A ACN, solution B phosphate buffer of pH 3.5 added few drops of Triethylamine in of buffer solution. The run time of 10 min was selected. The mobile phase composition keep on varying up to the 10 min of run time. The flow rate of 1.0 ml/min was used and Perkin Elmer series 200 UV/VIS detector wavelength was set at 250 nm. The retention time of Valsartan was found to be 5.19 min. The percentage recovery was found to be up to 99% to nearly 100% and percentage RSD was found to be less than 2.0%. Proposed method was validated for precision, accuracy, linearity range, robustness and ruggedness. The method was successfully applied for quantitative determination of valsartan in tablet dosage form.